Solution of Problem Pertaining to Optimum Control over Heat- and Mass Transfer Process - N. P. Voronova (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The purpose of the proposed investigation is a mathematical formulation a problem and solution of the problems pertaining to selection of operating conditions of heat- and mass transfer processes using numerical methods. Such methodology makes it possible to calculate how the function describing the state of the controlled medium should be changed in order to obtain a desired distribution within minimum period of time. Results of the given paper may be applied for description of drying, heating and other processes.